Тунгусская катастрофа: детали головоломки - Гладышева Ольга Гарибальдовна (Наука, 2011)
Экземпляры: КХ (20150508) / Инвентарный номер: 1095881 / Цена: / Сис.шифр: 22.6 / Авт.знак: Г 52 / ГРНТИ: 41 / ББК: 22.655